The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1007/s11628-011-0123-9
|View full text |Cite
|
Sign up to set email alerts
|

Social innovation, an analytical grid for understanding the social economy: the example of the Québec housing sector

Abstract: Over the past few decades, there has been renewed interest in the social economy, especially in relation to the employment crisis and the reshaping of State's interventions. The social economy plays an important role in solving new social problems with pioneering solutions, especially in the field of public services. It is important to better understand its innovative function. This article discusses the notion of social innovation and explains how it can be used as an analytical framework for understanding th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
67
0
15

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(86 citation statements)
references
References 12 publications
0
67
0
15
Order By: Relevance
“…However, in spite of this direct link, it is noteworthy to mention that the two variables do not depend on each other. This review found several authors who discuss social innovation without mentioning social entrepreneurship (Adams & Hess, 2010;Bouchard, 2012;Cajaiba-Santana, 2014;Froud et al, 2010;Linton, 2009;Spena & de Chiara, 2012). Additionally, social entrepreneurship is critical with respect to social issues, but it is not a key determinant of social innovation (Dawson & Daniel, 2010).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, in spite of this direct link, it is noteworthy to mention that the two variables do not depend on each other. This review found several authors who discuss social innovation without mentioning social entrepreneurship (Adams & Hess, 2010;Bouchard, 2012;Cajaiba-Santana, 2014;Froud et al, 2010;Linton, 2009;Spena & de Chiara, 2012). Additionally, social entrepreneurship is critical with respect to social issues, but it is not a key determinant of social innovation (Dawson & Daniel, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…In the papers reviewed, several authors discuss the relationship between social innovation and social development. They coincide in that both social innovation and social development seek to strengthen social structure and that social innovation facilitates social development (Adams & Hess, 2010;Bouchard, 2012;Cajaiba-Santana, 2014;Dacin et al, 2011;Dawson & Daniel, 2010;Froud et al, 2010;Maak & Stoetter, 2012).…”
Section: Methodology: Scoping Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the analytical dimensions of social innovations proposed by Tardif and Harrison (2005) and the classification of the actors developed by Rollin and Vincent (2007) can be considered adequate for understanding the formation of collective enterprises in the handicraft sector, since they permit the identification of the main elements within the solutions developed with a considerable number of actors, which had previously been noted by Bouchard (2012). The studied social innovations sought primarily to meet the income generation, employment and, in some cases, the social needs of the individuals involved.…”
Section: Final Remarksmentioning
confidence: 98%
“…It consists of a network with the participation of actors from the public, private and third sectors with complementary objectives, building social cohesion, changing social relations, and proposing new cultural orientations (Bouchard, 2012).…”
Section: Introductionmentioning
confidence: 99%